Cross‐Shore Distribution of the Wave‐Induced Circulation Over a Dissipative Beach Under Storm Wave Conditions. Issue 3 (19th March 2022) - Pezerat, Marc; Bertin, Xavier; Martins, Kévin; Lavaud, Laura
Abstract: This study explores the spatial distribution and the driving mechanisms of the wave‐induced cross‐shore flow within the shoreface and surf zone of a dissipative beach. Unpublished results from a field campaign carried out in early 2021 under storm wave conditions are presented and compared with the predictions from a state‐of‐the‐art phase‐averaged three‐dimensional circulation modeling system based on the vortex force formalism. Under storm wave conditions, the cross‐shore flow is dominated by a strong seaward‐directed current in the lower part of the water column. The largest current velocities of this return current are located in the surf zone, where the dissipation by depth‐induced breaking is most intense, but offshore‐directed velocities up to 0.25 m/s are observed as far as 4 km from the shoreline (≃12 m‐depth). Numerical experiments further highlight the key control exerted by non‐conservative wave forces and wave‐enhanced mixing on the cross‐shore flow across a transition zone, where depth‐induced breaking, whitecapping, and bottom friction all significantly contribute to the wave energy dissipation. Under storm conditions, this transition zone extended almost 6 km offshore and the cross‐shore Lagrangian circulation shows a strong seaward‐directed jet in the lower part of the water column, whose intensity progressively decreases offshore. In contrast, the surf zone edge appears clearly delimited under fair weather conditions and the seaward‐directed current is weakened by a near bottom shoreward‐directed current associated with wave bottom streaming in the shoaling region, such that the clockwise Lagrangian overturning circulation is constrained by an additional anti‐clockwise overturning cell at the surf zone edge. Plain Language Summary: As waves propagate toward the shore fluid parcels experience a net transport in the direction of wave propagation. This onshore mass transport is compensated by a near bed return flow, which dynamics remain poorly understood. This study combines measurements from a field campaign carried out in early 2021 in front of a gentle sloping beach and numerical modeling to explore the spatial distribution and the driving mechanisms of this wave‐induced cross‐shore flow. Both observations and model results show that the largest current velocities of this return current are located very close to the shoreline, where the wave breaking is the most intense, but values up to 0.25 m/s are observed as far as 4 km from the shoreline under storm conditions. Numerical experiments further highlight the key control exerted by the wave forces and the wave‐enhanced mixing, which induce very contrasted circulation patterns under fair weather or storm conditions and strongly constrain the vertical structure of the cross shore flow. Key Points: Field experiment at a dissipative beach with 6 m H m0 at breaking and undertows reaching 0.25 m/s as far as 4 km from the shoreline Accurate reproduction of the cross‐shore hydrodynamics using a phase‐averaged 3D circulation model Wave dissipation by breaking locally increases seaward‐directed flows by over 100% compared to the surface Stokes drift velocity